Targeting Cardiovascular Risk Factors Through Dietary Adaptations and Caloric Restriction Mimetics - Voglhuber, Julia; Ljubojevic-Holzer, Senka; Abdellatif, Mahmoud; Sedej, Simon (Frontiers in Nutrition, 2021)
The average human life expectancy continues to rise globally and so does the prevalence and absolute burden of cardiovascular disease. Dietary restriction promotes longevity and improves various cardiovascular risk factors, including hypertension, obesity, diabetes mellitus, and metabolic syndrome. However, low adherence to caloric restriction renders this stringent dietary intervention challenging to adopt as a standard practice for cardiovascular disease prevention. Hence, alternative eating patterns and strategies that recapitulate the salutary benefits of caloric restriction are under intense investigation. Here, we provide an overview of alternative interventions, including intermittent fasting, alternate-day fasting and the Mediterranean diet, along with their cardiometabolic effects in animal models and humans. We then present emerging pharmacological alternatives, including spermidine, NAD+ precursors, resveratrol, and metformin, as promising caloric restriction mimetics, and briefly touch on the mechanisms underpinning their cardiometabolic and health-promoting effects. We conclude that implementation of these feasible approaches holds the promise to attenuate the burden of cardiovascular disease and facilitate healthy aging in humans.